Analysis Of Teacher Strategies In Overcoming Primary School Students' Early Reading Learning Difficulties Using An Individual Approach - Irawati, Rika; Hadi, Sopiyan; Houtman, Houtman (LPPM Universitas PGRI Sumatera Barat, 2024)
This research was conducted to describe the strategies used by class teachers in overcoming reading learning difficulties of second grade students at SD Negeri 1 Sri Tanjung. This research employs descriptive qualitative research methods in the form of a case study. Qualitative research is also referred to as a naturalistic research method, as it is conducted in natural conditions. The findings of the research and subsequent discussion lead to the conclusion that a form of learning difficulty, specifically reading difficulties, was identified in Class II SDN Sritanjung. The reading difficulties observed in the field are classified as low-level reading difficulties. The strategies employed by the class teachers are not optimal, as evidenced by the persistence of difficulties in learning to read and write among a significant proportion of students. The teacher's strategy for introducing beginning reading employs a multi-modal approach, integrating the thickening of letters, the word wall method, reading book media, and a range of activities, including letter and word games, singing, the question-and-answer method, and the assignment method.